Microbiology of waterborne diseases : microbiological aspects and risks - Percival, Steven L.; Yates, M. V. (Marylynn V.); Williams, David W.; Chalmers, Rachel; Gray, N. F. (Elsevier/Academic Press, 2014)
The second edition of Microbiology of Waterborne Diseases describes the diseases associated with water, their causative agents and the ways in which they gain access to water systems. The book is divided into sections covering bacteria, protozoa, and viruses. Other sections detail methods for detecting and identifying waterborne microorganisms, and the ways in which they are removed from water, including chlorine, ozone, and ultraviolet disinfection. The second edition of this handbook has been updated with information on biofilms and antimicrobial resistance. The impact of global warming and climate change phenomena on waterborne illnesses are also discussed. This book serves as an indispensable reference for public health microbiologists, water utility scientists, research water pollution microbiologists environmental health officers, consultants in communicable disease control and microbial water pollution students. Focuses on the microorganisms of most significance to public health, including E. coli, cryptosporidium, and enterovirus. Highlights the basic microbiology, clinical features, survival in the environment, and gives a risk assessment for each pathogen. Contains new material on antimicrobial resistance and biofilms. Covers drinking water and both marine and freshwater recreational bathing waters.